Remembering routes: confronting spatial behaviours and sketch maps in individual and collective contexts - Quesnot, Teriitutea; Guelton, Bernard (Frontiers in Psychology, 2025)
This exploratory study addresses the following question: Is there an explanatory relationship between the chronological sequence in which individuals explore an environment and the way they subsequently draw a sketch map of that same environment? To answer it, we conducted a navigation experiment in La Plaine Saint-Denis (France) involving 118 participants tracked in real time, and divided into three groups: (1) solo exploration without instruments; (2) solo exploration with a mobile map; (3) collective exploration through a dedicated application. The comparison of the tracking data with the videos of the sketch map making shows that Group 1 participants drew the places they visited in the chronological order of their exploration. This tendency is less significant in Group 2, and absent in Group 3, suggesting that in the absence of a map and/or collective interactions, individuals who draw a sketch map tend to recall the route they have just taken.